IMPROVING STUDENTS’ ABILITY IN ENGLISH BASED ON LEARNING STYLEOF PRIVATE HIGHER EDUCATION INSTITUTIONS - Linda Septarina; Sushanty Saleh; Hery Yufrizal (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The objetives of the present research are firstly to find out whether there is any significant effect of students’ learning styles on their achievement of English at higher private institutions in Bandar Lampung. Secondly it tries to find out which students’ learning is more superior then the other students. The researh was conducted at 5 private higher education institutions in Lampung Province. The results showed that there was a significant effect of learning styles toward the students’ English  Achievement. The students with communicative learning style were more dominanat than students with other learning styles. Furthermore, the study also found out that students with authority oriented learning style gainrd the lowest achievement compared to other  studentsKey Words: Achievement of English, learnig syles, language abilities